Study on Parametrically Excited Microelectromechanical System in the Problems of Orientation of Moving Objects - Bakhtieva, L.; Bogolyubov, V. (Research Trends and Challenges in Physical Science Vol. 5, 2021)
The aim of the study is the motion dynamics analysis of a parametrically excited micromechanical gyroscope and exploration of the possibility of its use as a ground-based precision device for orienting mobile objects. A mathematical model of the microelectromechanical system (MEMS) has obtained, which performs the task of orienting mobile objects. A distinctive feature of the construction of such MEMS is its parametric excitation by modulating the static stiffness of the suspension of the sensitive element. Based on the analysis of model equations, the possibility of determining the direction of the true meridian with the required accuracy has shown. The results of numerical calculations have presented that allow not only to illustrate the operation of the device as a high-speed gyrocompass, but also to determine the conditions that ensure the stable operation of the device in the incoherent mode of its excitation.